2016
DOI: 10.1177/1535370216638770
|View full text |Cite
|
Sign up to set email alerts
|

Detection of inflammatory biomarkers in saliva and urine: Potential in diagnosis, prevention, and treatment for chronic diseases

Abstract: Inflammation is a part of the complex biological response of inflammatory cells to harmful stimuli, such as pathogens, irritants, or damaged cells. This inflammation has been linked to several chronic diseases including cancer, atherosclerosis, rheumatoid arthritis, and multiple sclerosis. Major biomarkers of inflammation include tumor necrosis factor, interleukins (IL)-1, IL-6, IL-8, chemokines, cyclooxygenase, 5-lipooxygenase, and C-reactive protein, all of which are regulated by the transcription factor nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 233 publications
0
79
0
2
Order By: Relevance
“…The high resistin level in obese people may be linked to the microbiota inhabiting the mouth as LPS from periodontopathogenic bacteria has been reported as an inducer for the expression of resistin [ 27 29 ]. Our study depended on noninvasive saliva sampling without invasive blood collection [ 40 ]. Further studies must be conducted in the future to compare the levels of resistin in the saliva and serum in both periodontally healthy and diseased patients in order to confirm the role of the periodontopathogenic bacteria in the induction of local resistin secretion in the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…The high resistin level in obese people may be linked to the microbiota inhabiting the mouth as LPS from periodontopathogenic bacteria has been reported as an inducer for the expression of resistin [ 27 29 ]. Our study depended on noninvasive saliva sampling without invasive blood collection [ 40 ]. Further studies must be conducted in the future to compare the levels of resistin in the saliva and serum in both periodontally healthy and diseased patients in order to confirm the role of the periodontopathogenic bacteria in the induction of local resistin secretion in the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Javaid et al 5 reported that saliva is a potential diagnostic tool due to its ease of collection and noninvasiveness. Moreover, salivary diagnostic tests could allow the screening of specific diseases in the whole population on a prompt basis 5‐7 …”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the identification of biomarkers for CNS inflammation in the context of a spectrum of brain diseases have demonstrated that these markers are detectable in the urine of patients. [15][16][17] Combining cfDNA analysis with identification of biomarkers of CNS inflammation holds the potential for a sensitive and specific approach for the diagnose NCC from a single urine sample.…”
Section: Discussionmentioning
confidence: 99%